The effects of varying inertial loadings on power variables in the flywheel romanian deadlift exercise - Brien, Joey; Browne, Declan; Earls, Des; Lodge, Clare (Biology of Sport, 2022)
The aim of this study was to investigate the effect of four different inertial loads (0.025, 0.050, 0.075, and 0.100 kg· m²) on concentric (CON) power, eccentric (ECC) power, and ECC overload in the flywheel Romanian deadlift (RDL). Fourteen recreationally trained males (27.9 ± 6.4 years, 90 ± 10.7 kg, 180.7 ± 5.5 cm) volunteered for the study. They had a minimum of two years of resistance training experience, although none had experience in flywheel inertia training (FIT). All participants performed the flywheel RDL on a flywheel device (kBox 3, Exxentric, AB TM, Bromma, Sweden). Each set was performed using different inertial loads, those being 0.025, 0.050, 0.075, and 0.100 kg·m². For CON, ECC power, and ECC overload, there was a significant difference (p < 0.001) between inertial loadings. In conclusion, results highlight that lower inertial load leads to higher peak CON and ECC power values, precisely 0.025 kg· m². Regarding ECC overload, medium to higher loads (0.050, 0.075, and 0.100 kg·m²) will lead to higher values.